Increased ER stress as a mechanism of retinal neurovasculopathy in mice with severe hyperhomocysteinemia - Tawfik, Amany (Austin J Clin Ophthalmol, 2014)
Hyperhomocysteinemia is implicated in retinal neurovascular diseases including arterial occlusive disease, venous occlusive disease and pseudoexfoliation glaucoma. The mechanism for these diseases is not known. Here we used hyperhomocysteinemic mice lacking the gene encoding cystathionine-beta-synthase (cbs (−/−)) to examine whether ER stress could be a mechanism for the retinal neurovasculopathy reported in these mice. Retinas of cbs(+/+) and cbs (−/−) mice (age: 3–5 wks) were used to investigate the expression of ER stress genes (BiP/GRP78, Perk, Atf6, Atf4, Ire1α, Chop) and the proteins they encode. The levels of poly(ADP-ribose) polymerase (PARP) and cleaved cysteine-aspartic proteases-3 (caspase-3), proteins known to be involved in apoptosis, were also examined. Quantitative reverse transcription polymerase chain reaction and western blotting revealed an increase in BiP/GRP78 and PERK in retinas of cbs (−/−) mice compared with cbs(+/+) mice. There was an elevation of CCAAT-enhancer-binding protein homologous protein (CHOP) in retinal cryosections of cbs (−/−) mice indicating apoptosis, which was confirmed by increased levels of PARP and cleaved caspase-3. The data suggest that the genes and proteins that are major players in the ER stress pathway, particularly the PERK pathway, are upregulated in retinas of cbs (−/−) mice. The data support a role for ER stress in the pathophysiology associated with the hyperhomocysteinemia-linked retinal disease.